The practice of islamic relationship marketing among takaful agents and its effect towards customer trust and commitment - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani (International Shariah Research Academy for Islamic Finance, 2014)
During the last three decades ‘relationship marketing’ has become more popular in the field of marketing. This marketing approach highlights the need of a company or business entity to maintain longterm relationships with customers. In the 1980s, the relationship marketing strategy was widely accepted as a new marketing paradigm as many companies began to shift their marketing strategy to one focused on maintaining existing customers (customer retention) rather than on acquiring new ones (Sheth, 2002). This strategy remains popular today as more companies continue to organise marketing campaigns geared towards establishing strong relationships with customers.